Technical evaluation of Turbuhaler® use in children with bronchial asthma: combination of a checklist and inhalation parameters - Lina Liang; Ruogang Huang; Yun Li; Zhufeng Wang; Kang Peng; Junfeng Lin; Feifei Huang; Xiaoyin Yao; Jinping Zheng; Yi Gao (BMC Pulmonary Medicine)
Abstract Background The Turbuhaler® is a dry powder inhaler (DPI) that is commonly used in the treatment of asthmatic patients aged 5 years and above. Nevertheless, the technique of using the Turbuhaler® in the real world remains ambiguous. This study aims to evaluate techniques in using Turbuhaler® by combining a checklist with inhalation parameters and to investigate the association between the patient characteristics and inhaler technique. Methods This study recruited asthmatic children aged 4 to 14 years who were using the Turbuhaler® from The First Affiliated Hospital of Guangzhou Medical University from August 2023 to August 2024. The technique of using Turbuhaler® was evaluated step by step, and the inhalation parameters of patients were subsequently tested. Influencing factors related to inhaler technique were analyzed by ordered logistic regression analysis. Results Of the 141 enrolled patients, 50 (35.5%) scored 10 points on the checklist. Overall, 105 (74.4%), 28 (19.9%) and 8 (5.7%) patients performed good, moderate, and poor inhaler technique, respectively. The three common improper steps were ‘‘exhale to residual volume’’ (35.5%), “inhale forcefully and deeply” (13.5%), “rinse mouth after inhalation” (13.5%). The three common inappropriate inhalation parameters were “Effective inspiratory time(EIT) < 2s” (90.8%), “Peak inspiratory flow rate(PIFR) < 60L/min” (41.8%), and “Breath-hold time(BHT) < 5s” (27.0%). In the three groups with good, moderate, poor inhaler techniques, 0, 2 (7.1%), and 2 (25.0%) patients did not reach the minimum PIFR. Meanwhile, 38 (36.2%), 15 (53.6%), and 6 (75.0%) patients did not reach the optimal PIFR, respectively. The results of ordered logistic regression analysis indicated that low medication adherence (P = 0.045), PIFR (P = 0.041), BHT (P = 0.003) and the duration of Turbuhaler® use (P = 0.009) were the primary factors influencing asthmatic children’s inhaler technique. Conclusion The improper use of inhalers and inappropriate inhalation parameters are common among asthmatic children. Using checklist and inhalation parameters enables a more comprehensive evaluation of the patients' inhalation maneuvers and inspiratory effort. Trial registration This study is registered at Chictr.org with the identifier number ChiCTR2200056579.